One-dimensional structure made of periodic slabs of SiO2/InSb offering tunable wide band gap at terahertz frequency range. (November 2019) - Razi, Sepehr; Ghasemi, Fatemeh
Abstract : Optical features of a semiconductor–dielectric photonic crystal are studied theoretically. Alternating layers of micrometer sized SiO2 /InSb slabs are considered as building blocks of the proposed ideal crystal. By inserting additional layers and disrupting the regularity, two more defective crystals are also proposed. Photonic band structure of the ideal crystal and its dependence on the structural parameters are explored at the first step. Transmittance of the defective crystals and its changes with the thicknesses of the layers are studied. After extracting the optimum values for the thicknesses of the unit cells of the crystals, the optical response of the proposed structures at different temperatures and incident angles are investigated. Changes of the defect layers' induced mode(s) are discussed by taking into consideration of the temperature dependence of the InSb layer permittivity. The results clearly reflect the high potential of the proposed crystals to be used at high temperature terahertz technology as a promising alternative to their electronic counterparts.